Subluminal Focal Lesions in Peyer's Patches in the Terminal Ileum of Pigs Fed With Different Physical Forms of One Same Diet - Cappai, Maria Grazia; Dimauro, Corrado; Arlinghaus, Michael; Sander, Saara J.; Pinna, Walter; Kamphues, Josef (Frontiers in Veterinary Science, 2020)
Retrograde backflow of cecum chyme and consequent ascendent colonization of the foregut may occur via the ileocecal valve (IV) under predisposing circumstances. The Peyer's patches (PPs) in the terminal ileum (TI) play a crucial role in targeting antigens and act as a first line of blockage of pathogens in the small intestine. In view of the established impact of the physical form of the diet (grinding and compaction of ingredients) on the physicochemical and microbiological composition of digesta throughout the different gastrointestinal tracts, special attention was paid to PP reaction following different dietary treatments. The aim of this study was to explore the effect of different physical forms of one diet (identical for botanical and chemical composition) administered to growing pigs on macro- and microscopic morphology of PPs in the last 3 cm of the TI, as a region of interest immediately close to the IV involved in the prevention of retrograde contamination of the small intestine. The diet effect was tested after 4 weeks of experimental feeding on PPs of 32 growing pigs, fed with four dietary treatments differing for the physical form: FP—finely ground pelleted diet (dMEAN, 0.463 mm); CM—coarsely ground meal diet (dMEAN, 0.880 mm); CP—coarsely ground pelleted diet (dMEAN, 0.836); and CE—coarsely ground extruded diet (dMEAN, 0.659). A higher prevalence of subluminal focal liquefactive necrosis (FLN) in the last 3 cm of the TI was observed in pigs fed with the CE and the FP diet (n. 3/8 or 37.5% and n. = 1/8 or 12.5%, respectively) (p = 0.076). FLN negatively and significantly correlated with the pH value of digesta of the last part of the small intestine (ρ = −0.361; p = 0.026). All animals enrolled appeared clinically healthy throughout the trial. Growth performance were not affected by the different dietary treatments, but fecal dry matter and pH values were affected in a significant way. Results about the morphology of PPs assessed in this trial can be suggestive of the physical form of the diet as a contributing factor to the onset of different antigenic potentials of the intestinal chyme.